Microbial regulation of nutrient cycling potential and soil amelioration after Morchella cultivation in saline-alkali soils of Ningxia - Yifan Wu; Xiaoli Yang; Yaya Zhang; Chunyan Xu (Applied Soil Ecology, 2026)

Cracking Behavior and Failure Characteristics of Rock–Coal–Rock Composites with Varying Thickness - Xuan Cui; Shengli Yang; Heinz Konietzky; Aoxiang Wang; Chunyu Duan (Rock Mechanics and Rock Engineering, 2026)

Intelligent monitoring of coastal outfalls via multi-source remote sensing image fusion - Ruisheng Yang; Haolan Zhou; Shicheng Zhao; Li Yang (Marine Pollution Bulletin, 2026)

Shifts from phosphorus to nitrogen limitations of microbial metabolism with the forest development of Phoebe bournei plantations - Zhengyang Zheng; Bowen Min; Zehao Li; Fanghai Luo; Hechuan Wang; Ying Zhang; Ziqiao Yang; Hanbin Wu; Lili Yang; Gongxiu He; Lei Lv; Li Ji (Applied Soil Ecology, 2026)

The Roles of SOCS in Teleost Immunity: Cytokine Regulation and Host Defense - Ying Zhang; Li Yang; Xiuying Cui; Feng Gao; Yanjing Zhao; Xianghui Kong (Reviews in Aquaculture, 2026)
The Suppressor of Cytokine Signaling (SOCS) family comprises key regulatory molecules which are essential for maintaining immune homeostasis in vertebrates. Owing to a teleost‐specific whole‐genome duplication event, SOCS family members exhibit higher diversity and significant functional differentiation, forming a complex and precise immune regulatory network. This review comprehensively summarizes the current understanding of SOCS‐mediated cytokine regulation and host defense mechanisms in teleosts. SOCS proteins, particularly SOCS1 and SOCS3, exert dual regulatory effects in antiviral and antibacterial immunity as well as in inflammatory balance by negatively modulating key pathways such as JAK/STAT and NF‐κB, exemplifying their “double‐edged sword” role. Moreover, we provide the first comprehensive synthesis of environmental regulation of SOCS expression in teleosts, integrating emerging evidence on how to modulate SOCS levels after temperature stress, neuroendocrine activation via cortisol, hypoxia, and chemical pollutants and how to link environmental conditions to immune competence. This environmental perspective supplies direct implications for understanding stress‐induced immunosuppression in aquaculture. Finally, we discuss the potential application of targeting SOCS signaling in aquaculture practices, including applications in disease‐resistant breeding, vaccine development, and immunostimulant design. In‐depth understanding of SOCS diversity and function in fish will provide novel molecular insights and innovative strategies for precise disease control and sustainable aquaculture.

Recent advances in machine/deep learning frameworks for biochar application in soil amendment and remediation - Muhammad Waqas; Mohsin Nawaz; Rongli Yang; Waseem Tariq; Muhammad Nauman Tahir; Shakeel Ahmad (Applied Soil Ecology, 2026)

Symmetric responses of microbial carbon and nutrient limitations to warming and cooling in boreal forests: Insights from a transplant experiment - Sen Lu; Dongdong Zhang; Shuanglin Zhao; Ziqiao Yang; Ying Zhang; Lili Yang; Gongxiu He; Li Ji (Applied Soil Ecology, 2025)